50 years of radiation protection and nuclear power in Switzerland: a brief history. (17th July 2006) - Volkle, Hansruedi
This article presents a short history of research in nuclear physics as well as of 50 years of nuclear power and radiation protection in Switzerland. After the International Conference 'Atoms for Peace' held in 1955 in Geneva the first research reactor was installed in Switzerland. A national environmental radioactivity monitoring programme was started in 1956. Today some 40% of the electricity is produced by nuclear power. In 1986, the southern part of Switzerland was most burdened by radioactive fallout from the Chernobyl Accident. Fortunately, the integral average radiation doses to the population remained below 0.5 milli-Sievert. As in other western countries there was a vigorous debate in Switzerland in the 1980s and 1990s about nuclear power, nuclear safety and the safe storage of radioactive waste.